Challenges Faced by the Police in Resolving Theft Offenses Committed by - Apriyansha Putra Ali; Lisnawaty W. Badu; Muhamad Khairun Kurniawan Kadir (Damhil Law Journal, 2025)
This study discusses the role of the police in handling criminal acts of theft committed by minors, with a focus on the implementation of diversion as an alternative dispute resolution in accordance with the mandate of Law No. 11 of 2012 on the Juvenile Criminal Justice System. The research employs a juridical-empirical method with a qualitative descriptive approach, using literature study, interviews with law enforcement officers, and field data analysis. The findings of the study reveal several key points: first, the police play a strategic role as the initial gatekeepers in determining the course of cases; however, they are still constrained by a lack of competent juvenile investigators, specialized detention facilities, and limited support from psychologists or social workers. Second, the implementation of diversion in juvenile theft cases has not been optimal, due to resistance from victims or their families who perceive justice can only be achieved through formal criminal prosecution. Third, the legal culture that remains retributive, the lack of understanding among law enforcement officers and the public regarding restorative justice, and the weak coordination between institutions (police, prosecutors, judges, and social institutions) lead to many juvenile cases continuing to court, even though they meet the criteria for diversion. Nevertheless, the research also finds that successful diversion can have a significant positive impact: children are spared from criminal stigma, victims receive recovery, and social order is restored to harmony. Therefore, comprehensive reform is needed through capacity building for law enforcement, strengthening supporting facilities, and public education, so that the implementation of diversion truly becomes an instrument of justice that protects the future of children.